Psychometric properties of the Polish version of the Self-Pluralism Scale (SPS) - Agnieszka E. Łyś; Hubert Suszek; Krzysztof Fronczyk (Current Issues in Personality Psychology, 2021)
Introduction The Self-Pluralism Scale (SPS) measures the declared degree of self-pluralism, visible already in William James’s works. Self-pluralism refers to the degree to which one perceives oneself as typically feeling, behaving, and being different, in different situations, and at different times. The purpose of the current study was to evaluate the psychometric properties of the Polish version of the SPS.